Tunable ultra-wide band-stop filter based on single-stub plasmonic-waveguide system. (16th September 2016) - Chen, Zhiquan; Li, Hongjian; Li, Boxun; He, Zhihui; Xu, Hui; Zheng, Mingfei; Zhao, Mingzhuo
Abstract: A nanoscale plasmonic filter based on a single-stub coupled metal–dielectric–metal waveguide system is investigated theoretically and numerically. A tunable wide band-stop can be achieved by loading a metal bar into the stub. The band-stop originates from the direct coupling between the resonance modes. The bandwidth and the center wavelength of the band-stop can be tuned by changing the parameters of the metal bar. Compared with previously reported filters, the plasmonic system has the advantages of easy fabrication and compactness. Our results indicate that the proposed system has potential to be utilized in integrated optical circuits and tunable filters.